FUNGSI DAN MAKNA SIMBOL-SIMBOL DALAM PALINGGIH PADMASANA PERSPEKTIF KAJIAN BUDAYA - Putera Semadi, Anak Agung Gde (Widya Accarya, 2021)
Abstract Palinggih Padmasana is a sanctified building to worship Ida Sang Hyang Widhi Wasa/God Almighty in His various manifestations. It does not only has a varying fomrs, but olso defferent designation , function, and meaning of symbols which differ based on its location. Historycally, the existence of this palinggih was only known around 15th century especially during the reigin of Dalem Waturenggong which was indicated by the arrival of a powerful Shiwa priest to Bali named Danghyang Dwijendra with a sacred mission of perfecting the order of Hindu life from Tri Murti to Tri Purusa concept. Each function and symbol in palinggih Padmasana truly reflects the nobility of invaluable meaning, therefore, Padmasana is a symbol of the universe for Hindus. Through the perspective of cultural sytudies which is accompained by the implementation of descriptive analysis method, this research topic was successfully studied critically, logically, and systematically.